Molva dypterygia - Carneiro, Miguel; Martins, Rogélia; Landi, Monica; Costa, Filipe O. (Zenodo, 2014)
Molva dypterygia (Pennant, 1784) – Blue ling; Donzela-azul ① , ② This species is regarded as being present north of the Azores (Hareide & Garnes 2001), in the PECS area (Mid-Atlantic Ridge, 43º-44ºN). : Published as part of Carneiro, Miguel, Martins, Rogélia, Landi, Monica & Costa, Filipe O., 2014, Updated checklist of marine fishes (Chordata: Craniata) from Portugal and the proposed extension of the Portuguese continental shelf, pp. 1-73 in European Journal of Taxonomy 73 on page 37, DOI: 10.5852/ejt.2014.73, http://zenodo.org/record/3866515 : {"references": ["Hareide N. - R. & Garnes G. 2001. The distribution and catches rates of deep water fish along the Mid- Atlantic Ridge from 43 to 61 \u00baN. Fisheries Research 51: 297 - 310."]}